Secularisation: process, program, and historiography. Issue 1 (2nd January 2017) - Hunter, Ian
ABSTRACT: Today's dominant academic use of the term 'secularisation' refers to an epochal process that transformed a society based on Christian faith to one grounded in human reason. This paper argues that 'secularisation' had not been used in this sense prior to the 1830s, and that no such process has been shown to have taken place in early modernity. This new use of the term was in fact internal to rival secularising and sacralising programs. The notion of an epochal rationalisation of society was thus invoked by secularists seeking to turn a factional campaign into an historical process. Their sacralising opponents employed the same strategy when they claimed that this process contained a desecularising counter-current, or that secularisation was secretly grounded in an alienated religion whose de-alienation held the promise of a post-secular age. This suggests that until they can adduce evidence of an epochal rationalisation of society in early modernity, histories of secularisation should be regarded as disguised program-statements for rival cultural-political factions in the present.